Delphi study to identify consensus on patient selection for hydrogel rectal spacer use during radiation therapy for prostate cancer in the UK. Issue 7 (20th July 2022) - Payne, Heather Ann; Jain, Suneil; Peedell, Clive; Edwards, Albert; Thomas, James Andrew; Das, Prantik; Hansson Hedblom, Amanda; Woodward, Emily; Saunders, Rhodri; Bahl, Amit
Abstract : Objectives: To identify consensus on patient prioritisation for rectal hydrogel spacer use during radiation therapy for the treatment of prostate cancer in the UK. Design: Delphi study consisting of two rounds of online questionnaires, two virtual advisory board meetings and a final online questionnaire. Setting: Radical radiation therapy for localised and locally advanced prostate cancer in the UK. Participants: Six leading clinical oncologists and one urologist from across the UK. Interventions: Rectal hydrogel spacer. Primary and secondary outcome measures: None reported. Results: The panel reached consensus on the importance of minimising toxicity for treatments with curative intent and that even low-grade toxicity-related adverse events can significantly impact quality of life. There was agreement that despite meeting rectal dose constraints, too many patients experience rectal toxicity and that rectal hydrogel spacers in eligible patients significantly reduces toxicity-related adverse events. However, as a consequence of funding limitations, patients need to be prioritised for spacer use. A higher benefit of spacers can be expected in patients on anticoagulation and in patients with diabetes or inflammatory bowel disease, but consensus could not be reached regarding patient groups expected to benefit less. While radiation therapy regimen is not a main factor determining prioritisation, higher benefit is expected in ultrahypofractionated regimens. Conclusion: There is a strong and general agreement that all patients with prostate cancer undergoing radical radiation therapy have the potential to benefit from hydrogel spacers. Currently, not all patients who could potentially benefit can access hydrogel spacers, and access is unequal. Implementation of the consensus recommendations would likely help prioritise and equalise access to rectal spacers for patients in the UK.